Popularity-driven science journalism and climate change: A critical discourse analysis of the unsaid. (March 2018) - Molek-Kozakowska, Katarzyna
Highlights: Popular science journalism eliminates some information for the sake of newsworthiness. Critical analysis concerns also what is missing, dismissed or backgrounded in discourse. Popular coverage of climate change is discursively different from institutional sources. Thematic, lexical, grammatical and compositional devices are used for backgroundng. Frames, narratives and news values used in popular articles discourage mobilization. Abstract: This study traces popularity-driven coverage of climate change in New Scientist with the special aim of identifying which aspects of the issue have been backgrounded. Unlike institutional communication or quality press coverage of climate change, commercial science journalism has received less attention with respect to how it frames the crisis. Assuming that the construction of newsworthiness in popular science journalism requires eliminating, or at least obscuring, some alienating information, the study identifies prevalent frames, news values and discursive strategies in the outlet's most-read online articles on climate change (2013–2015). With the official statement of the World Meteorological Organization (2014) as a reference, it considers which dimensions of the coverage have been backgrounded, and illustrates how language is recruited to de-emphasize some representations through implicitness, underspecification, or syntactic and compositional devices. It finds that the coverage relies on threat frames, privileges novelty and the timeliness and impact of climate science, avoids responsibility and adaptation frames, and endorses the so-called progress narrative. It discusses how this may forestall social and personal mobilization by placing trust in science institutions and technologies to confront the crisis.